Sevoflurane-Induced miR-211-5p Promotes Neuronal Apoptosis by Inhibiting Efemp2. (November 2021) - Shen, Yousu; Zhou, Tao; Liu, Xiaobing; Liu, Yanlong; Li, Yaqi; Zeng, Dewu; Zhong, Wensheng; Zhang, Mingsheng
Sevoflurane exposure can result in serious neurological side effects including neuronal apoptosis and cognitive impairment. Although the microRNA miR-211-5p is profoundly upregulated following sevoflurane exposure in neonatal rodent models, the impact of miR-211-5p on neuronal apoptosis and cognitive impairment postsevoflurane exposure has not yet been elucidated. Here, we found that sevoflurane upregulated miR-211-5p and downregulated EGF-Containing Fibulin Extracellular Matrix Protein 2 (Efemp2, Fibulin-4) levels in vitro and in vivo. Sevoflurane's effect on miR-211-5p expression was based on enhancing primary miR-211 transcription. miR-211-5p targets Efemp2's mRNA 3′-untranslated region, reducing Efemp2 expression. RNA immunoprecipitation revealed significant enrichment of the miR-211-5p:Efemp2 mRNA dyad in the RNA-induced silencing complex. miR-211-5p mimics downregulated Efemp2, leading to phosphorylation of Smad2 and Smad3, upregulation of pro-apoptotic Bim, and mitochondrial release of allograft inflammatory factor 1 and cytochrome C. In contrast, miR-211-5p hairpin inhibitor (AntimiR-211-5p) negatively regulated this apoptotic pathway and reduced neuronal apoptosis in an Efemp2-dependent manner. Sevoflurane-exposed mice administered AntimiR-211-5p displayed reduced cortical apoptosis levels and near-term cognitive impairment. In conclusion, sevoflurane-induced miR-211-5p promotes neuronal apoptosis via Efemp2 inhibition. Summary statement: This study revealed the significance of sevoflurane-induced increases in miR-211-5p on the promotion of neuronal apoptosis via inhibition of Efemp2 and its downstream targets.